„Biuletyn Szadkowski” – piętnaście lat działalności lokalnego czasopisma naukowego - Andrysiak, Ewa (Biuletyn Szadkowski, 2017)
In the article the author reminds the initiative to create a local journal of scientific Fri. “Biuletyn Szadkowski” constituent people, including the initiator of the project Tadeusz Marszał, the editors and authors of the circle and a rich thematic content. The magazine appeared in 1991 and is issued by the Municipal Office in Szadek. It is interdisciplinary, but dominated by historical texts.